2021
DOI: 10.1371/journal.pone.0253278
|View full text |Cite
|
Sign up to set email alerts
|

Can a social media intervention improve online communication about suicide? A feasibility study examining the acceptability and potential impact of the #chatsafe campaign

Abstract: There is a need for effective and youth-friendly approaches to suicide prevention, and social media presents a unique opportunity to reach young people. Although there is some evidence to support the delivery of population-wide suicide prevention campaigns, little is known about their capacity to change behaviour, particularly among young people and in the context of social media. Even less is known about the safety and feasibility of using social media for the purpose of suicide prevention. Based on the #chat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 59 publications
1
46
0
Order By: Relevance
“…The results also have implications for social media companies, which have a responsibility to be aware of the vulnerability of some users and take reasonable steps to promote safety. Tools such as the #chatsafe guidelines and accompanying social media campaign [52][53][54] may have an important role here and speak to the utility of providing mental health support to young people entirely via social media [54].…”
Section: Discussionmentioning
confidence: 99%
“…The results also have implications for social media companies, which have a responsibility to be aware of the vulnerability of some users and take reasonable steps to promote safety. Tools such as the #chatsafe guidelines and accompanying social media campaign [52][53][54] may have an important role here and speak to the utility of providing mental health support to young people entirely via social media [54].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of different approaches will be applied by the research team to build awareness, engagement, and integration with the community, based on local needs, desires, and resources available [ 45 ]. The collaborative consultation with sites is critical in discussing optimal dissemination methods through social media, podcasts, surveys, and consistent messaging to the local community [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…There were also a number of studies that focused on various social media platforms, including YouTube and Reddit, some of which also adopted novel approaches [ 29 31 ]. The role of the media, and in particular social media, has generated much interest in recent years with a number of studies examining both the potential harms and benefits associated with social media when it comes to suicide prevention [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…As as result, unfortunately suicide prevention research that actively engages consumers in a meaningful way remains rare [ 40 ]. In this collection whilst most of the studies would have included consumers as passive participants, a few also specifically sought to examine the perspectives of those with lived experience either of feeling suicidal themselves [ 41 ] or of having been bereaved by suicide [ 42 ], and the study by LaSala et al reported having partnered with young consumers on the development of the intervention being tested [ 31 ]. That said disappointingly, but perhaps unsurprisingly, none reported including consumers as research partners and to the best of our knowledge no studies were user-led.…”
Section: Introductionmentioning
confidence: 99%